2024
DOI: 10.1007/jhep04(2024)146
|View full text |Cite
|
Sign up to set email alerts
|

Large black hole entropy from the giant brane expansion

Matteo Beccaria,
Alejandro Cabo-Bizet

Abstract: We show that the Bekenstein-Hawking entropy of large supersymmetric black holes in AdS5 × S5 emerges from remarkable cancellations in the giant graviton expansions recently proposed by Imamura, and Gaiotto and Lee, independently. A similar cancellation mechanism is shown to happen in the exact expansion in terms of free fermions recently put-forward by Murthy. These two representations can be understood as sums over independent systems of giant D3-branes and free fermions, respectively. At large charges, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…where s a,b are Stirling number of the first kind and P k are twisted Weierstrass functions defined in (A. 16). It can be shown that the index expression (2.6) does not depend on the choice of the auxiliary fugacity w and special choices of w may simplify expressions.…”
Section: Jhep05(2024)282mentioning
confidence: 99%
See 2 more Smart Citations
“…where s a,b are Stirling number of the first kind and P k are twisted Weierstrass functions defined in (A. 16). It can be shown that the index expression (2.6) does not depend on the choice of the auxiliary fugacity w and special choices of w may simplify expressions.…”
Section: Jhep05(2024)282mentioning
confidence: 99%
“…In the simplest example of four dimensional N = 4 U(N ) super Yang-Mills (SYM) theory dual to type IIB superstring in AdS 5 × S 5 , finite N effects originate from wrapped D3 brane states maximally stretched in S 5 called giant gravitons [13] and having charge of order JHEP05(2024)282 N . 1 From the corresponding giant-graviton expansion of the index, it is possible to reproduce the entropy of dual black holes in AdS 5 × S 5 as first shown in [15] for small black holes with charge Q ≪ N 2 and later generalized to black holes with charge Q ∼ N 2 , first in [16], using a large-charge expansion, and later in [17], using a large N expansion. Recently, the giant graviton expansion has also been described by enumerating BPS geometries studying bubbling solutions in supergravity [18,19].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation